1984
DOI: 10.1139/v84-018
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of 13C and 15N nuclear magnetic resonance chemical shifts with polarographic reduction potentials of para-substituted benzenediazonium salts and their electronic structures

Abstract: . Can. J. Chem. 62, 92 (1984). Carbon-13 and nitrogen-15 nmr chemical shifts of benzenediazonium salt and its para-substituted derivatives have been measured in sulfolane solutions. The chemcial shifts of I3C 1 correlate linearly with the polarographic half-wave potentials. This relation indicates the linear increase of electron densities at Cl with the increase of electron-donating power of the substituents. Non-linear relationships between "N shifts of both nitrogen nuclei and the half-wave potentials were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…nance of the N-acetyl groups present. The two remaining lines, similar to those obtained for 14N and in agreement with the literature (Duthaler et al, 1978;Elofson et al, 1984), clearly indicate the presence of a diazonium salt derivative of Ñ-AcTyr.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…nance of the N-acetyl groups present. The two remaining lines, similar to those obtained for 14N and in agreement with the literature (Duthaler et al, 1978;Elofson et al, 1984), clearly indicate the presence of a diazonium salt derivative of Ñ-AcTyr.…”
Section: Resultssupporting
confidence: 90%
“…Comparison of the results given in Table I with the literature (Duthaler et al, 1978; Elofson et al, 1984) and in particular the presence of quaternary carbons at 94 and 168 ppm enable the following diazonium structure to be proposed:…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…When this process was repeated with aniline-15 N, the reaction monitoring step revealed the detection of hyperpolarized responses for both of the 15 N centers in the diazo product at δ N 315.0 and 232.6 in agreement with the literature (Figure 4a). 106 The hyperpolarization of both of the 15 N sites happens even though aniline itself was not hyperpolarized. Consequently, efficient polarization transfer between them takes place during their time as a coupled spin pair at low field.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Subsequently, X-ray studies have consistently shown the N-N distance, regardless of subst~tution patterns pr the nature of the anion, remains in the range I .O8 to 1.14 A, which is indicative, when compared to the dinitrogen distance of 1.097 A ( l ) , of the N-N triple bond remaining largely intact in the ground state. In recent years "C and ''N I I nmr studies (2,3) have suggested that resonance form "D" is a major contributor to the ground state. An important com-…”
Section: Introductionmentioning
confidence: 99%